Organisational changes in the Latxa breeding programme to introduce selection for milk quality - Ugarte E.; Legarra A.; Arrese F. (Breeding programmes for improving the quality and safety of products. New traits, tools, rules and organization?, 2003)
This paper presents the evolution and changes in the organisational structure of the genetic improvement program of the Latxa breed from 1982 to 2001. The most important aspects are emphasized in order to show how the organisation must be in accordance with the dimension of the program and with the production system of the breed. Changes in methodology and in personnel are shown. It is also shown that the financial support by the administration is essential in the first steps of the program.
Meeting of the Sub-Network on Genetic Resources of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2002/05/9-11, Sassari (Italy)